Strategi Inovasi Produk dan Pemasaran Digital dalam Meningkatkan Omzet UMKM Sate Maranggi Frozen di Kabupaten Purwakarta.: Penelitian - Aldilla Aisyah Anggraini; Lina Budiarti; Siti Nurhabiba; Yulianto Hadi (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The Frozen Maranggi Satay Micro, Small, and Medium Enterprise (MSME) in Purwakarta, established in 2023, demonstrates product innovation relevant to modern frozen food trends. However, this business faces significant challenges in financial governance (manual and unstructured record keeping) and localized digital marketing. This Community Practice Lecture (KPB-PKL) activity aims to address these weaknesses through direct mentoring. The methods used were observation, in-depth interviews, and applied coaching during the period August–October 2025. The intervention results demonstrated success in developing a daily cash recording format and a simple Profit and Loss Report for September 2025, as well as optimizing social media through direct contact linking. The conclusion shows that strengthening financial governance and digital marketing integration are crucial prerequisites for MSMEs to increase competitiveness, support accurate managerial decisions, and expand market reach beyond local boundaries. With a well-organized financial foundation and broader marketing reach, the Sate Maranggi Frozen MSME is expected to be able to transform into a scalable business and be ready to face regional competition. As a follow-up, it is recommended that MSMEs begin to consider the integration of a simple Point of Sale (POS) system and explore national marketplaces to accelerate business growth and achieve long-term financial stability. Substantively, this KPB-PKL activity has increased the financial and digital literacy of MSME owners, shifting their mindset from simply selling to data-driven business management. As a follow-up, it is recommended that MSMEs begin to consider the integration of a simple Point of Sale (POS) system and explore national marketplaces to accelerate business growth and achieve long-term financial stability, and help MSME finances.